2016
DOI: 10.4103/0019-5154.185764
|View full text |Cite
|
Sign up to set email alerts
|

Distant skin metastases from carcinoma buccal mucosa: A rare presentation

Abstract: Cancer of the oral cavity makes up approximately 30% of all head and neck region tumors. Skin metastasis is rare with an incidence ranging between 0.7% and 2.4%. Skin metastasis usually occurs in the neck, scalp, and over the skin near the primary site. We report a patient with carcinoma left buccal mucosa who presented with distant skin metastases to the right side chest wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…3,4,40 Furthermore, skin metastasis via infiltration of cancer cells is rarely observed, with an incidence ranging between 0.7% and 2.4%, especially in buccal mucosal carcinoma. [41][42][43] Because topical treatment has the advantage of being able to be applied many times a day by the patient, miR-634 ointment may be a minimally invasive topical medication for patients with a reduced quality of life due to bleeding and odorous exudates from skin infiltration. 44 Regarding miR therapeutics, there is a concern that "too many targets for miRNA effect" (TMTME) caused by the repression of multiple target genes may lead to unexpected adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,40 Furthermore, skin metastasis via infiltration of cancer cells is rarely observed, with an incidence ranging between 0.7% and 2.4%, especially in buccal mucosal carcinoma. [41][42][43] Because topical treatment has the advantage of being able to be applied many times a day by the patient, miR-634 ointment may be a minimally invasive topical medication for patients with a reduced quality of life due to bleeding and odorous exudates from skin infiltration. 44 Regarding miR therapeutics, there is a concern that "too many targets for miRNA effect" (TMTME) caused by the repression of multiple target genes may lead to unexpected adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…These case reports also include those cases that presented upfront with cutaneous metastasis in primary settings. Srinivasan et al reported a case with carcinoma of the left buccal mucosa with distant cutaneous metastases to the right-side chest wall, post-treatment at four months [ 1 ]. In general, distant metastases of head and neck squamous cell carcinoma (HNSCC) spread to other sites, and among them, the most common sites of distant metastases are usually the lung, liver, and bone.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cavity carcinoma accounts for 30% of all head-and-neck cancers [ 1 ]. It is more common in Southeast Asia because of the widespread use of tobacco (in any form), betel nuts, etc., especially in India [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of cutaneous metastases is associated with a very poor prognosis. Median survival from onset of cutaneous metastases ranges from three to seven months, with zero percent one year survival rate [1] . Treatment is palliative and surgical excision, radiotherapy and chemotherapy have all been used depen ding on the clinical circumstances [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Skin metastasis is rare with an incidence ranging between 0.7% and 2.4%. Skin metastasis usually occurs in the neck, scalp, and over the skin near the primary site [1] . The most common mode of spread of SCCHN (Squamous cell carcinoma of Head and Neck) is via regional lymph nodes to the cervical drainage areas [2] .…”
Section: Introductionmentioning
confidence: 99%